The Role of Transformational Leadership in Improving School Quality at SDN Cirendeu 02 - Nur Atik Azkiyah; Hasyim Asy’ari (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the role of transformational leadership in improving school quality at SDN Cierendu 02 South Tangerang. In this study, data were obtained through interviews with the principal. This study used a qualitative descriptive method. The results of the study showed that the application of transformational leadership style brought significant changes at SDN Cirendeu 02 South Tangerang, especially in improving discipline, communication, collaboration and efficiency of school programs that directly impacted the improvement of quality at SDN Cirendeu 02 South Tangerang.